Mechanical behavior of ropes based on polypropylene (PP) and poly(ethylene terephthalate) (PET) multifilament yarns for Achilles tendon partial substitution. (June 2020) - Morais, D.S.; Cruz, J.; Fangueiro, R.; Lopes, H.; Guedes, R.M.; Lopes, M.A.
Abstract: In some clinical cases, attending to the type and extension of the Achilles tendon injury, a partial replacement of the tissue may be needed. Driven by this, the authors developed different structures based on polypropylene (PP) or poly (ethylene terephthalate) (PET) multifilament yarns, using a textile technology-based technique, in order to mimic the fibrous structure of tendons. Those structures are based on a core/shell system, being the core composed by several sub-components (braids) and the shell based on braided yarns enclosing the core. It was observed that the load at failure of ropes is mainly defined by the number of yarns that compose it, but the strain level is mostly influenced by the production take-up rate of the core braids and consequently by the braid angle. The ropes stiffness level results from a combination of the yarns number and braid angle of the core braids. The structure based on PET yarns revealed a non-linear force-strain curve similar to a typical curve of a natural Achilles tendon (AT), presenting a load at failure, strain to failure and stiffness levels very promising for AT replacement. Moreover, the PET rope also revealed a very promising fatigue and appropriate creep resistance for the final application, being in accordance with what has been reported for native AT.